CDC20 promotes bone formation via APC/C dependent ubiquitination and degradation of p65. (12th August 2021) - Du, Yangge; Zhang, Min; Liu, Xuejiao; Li, Zheng; Hu, Menglong; Tian, Yueming; Lv, Longwei; Zhang, Xiao; Liu, Yunsong; Zhang, Ping; Zhou, Yongsheng
Abstract: The E3 ubiquitin ligase complex CDC20‐activated anaphase‐promoting complex/Cyclosome (APC/C CDC20 ) plays a critical role in governing mitotic progression by targeting key cell cycle regulators for degradation. Cell division cycle protein 20 homolog (CDC20), the co‐activator of APC/C, is required for full ubiquitin ligase activity. In addition to its well‐known cell cycle‐related functions, we demonstrate that CDC20 plays an essential role in osteogenic commitment of bone marrow mesenchymal stromal/stem cells (BMSCs). Cdc20 conditional knockout mice exhibit decreased bone formation and impaired bone regeneration after injury. Mechanistically, we discovered a functional interaction between the WD40 domain of CDC20 and the DNA‐binding domain of p65. Moreover, CDC20 promotes the ubiquitination and degradation of p65 in an APC11‐dependent manner. More importantly, knockdown of p65 rescues the bone loss in Cdc20 conditional knockout mice. Our current work reveals a cell cycle‐independent function of CDC20, establishes APC11 CDC20 as a pivotal regulator for bone formation by governing the ubiquitination and degradation of p65, and may pave the way for treatment of bone‐related diseases. Synopsis: This study reveals a cell‐cycle independent function of CDC20 and identifies APC11 CDC20 as a positive regulator of bone formation. Cdc20 conditional knockout mice exhibit decreased bone formation and impaired bone regeneration after injury. The WD40 domain of CDC20 interactes with the RHD domain of p65. CDC20 promotes the ubiquitination and degradation of p65 in an APC11‐dependent manner. Abstract : This study reveals a cell‐cycle independent function of CDC20 and identifies APC11 CDC20 as a positive regulator of bone formation.